Reconciliation in Southern Africa : the role of the Afrikaans Churches. A historical and analytical study of the contributions of the Afrikaans Churches to the process of reconciliation in Southern Africa, with special reference to their response to the work of the Truth and Reconciliation Commission - Meiring, Piet (Pieter Gerhard Jacobus), 1941- (University of Pretoria, 2013)
Thesis (PhD)--University of Pretoria, 2008.